Lonesome Dove : A Novel - McMurtry, Larry (New York : Simon & Schuster Paperbacks, 2010)
Chronicles a cattle drive in the nineteenth century from Texas to Montana, and follows the lives of Gus and Call, the cowboys heading the drive, Gus's woman, Lorena, and Blue Duck, a sinister Indian renegade.
"With a new preface by the author"--Cover.
Keywords: Cowhands -- Fiction; Western stories